2018
DOI: 10.2217/pgs-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Implementation of CYP2C19 Genotyping in Patients Using Antiplatelet Therapy

Abstract: CYP2C19 genotyping is feasible in everyday clinical practice, both in the acute and non-acute settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…For the CYP2C19*2 and *3 polymorphisms, point-of-care and laboratory-based testing is available, which makes it feasible to tailor antiplatelet therapy at the bedside. [46][47][48] The recently published randomized, open-label, assessor-blinded CYP2C19 Genotype-Guided Antiplatelet Therapy in ST-Segment Elevation Myocardial Infarction Patients-Patient Outcome after Primary PCI (POPular Genetics) trial tested a strategy of CYP2C19-guided antiplatelet therapy in 2,488 patients with ST-segment elevation myocardial infarction undergoing primary PCI, prescribing ticagrelor or prasugrel to CYP2C19*2 or *3 LOF allele carriers and clopidogrel to noncarriers, in comparison to a standard treatment arm in which all patients were prescribed ticagrelor or prasugrel. 17 The study showed a significant lower event rate for bleeding events in the genotype-guided arm, without increase in thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…For the CYP2C19*2 and *3 polymorphisms, point-of-care and laboratory-based testing is available, which makes it feasible to tailor antiplatelet therapy at the bedside. [46][47][48] The recently published randomized, open-label, assessor-blinded CYP2C19 Genotype-Guided Antiplatelet Therapy in ST-Segment Elevation Myocardial Infarction Patients-Patient Outcome after Primary PCI (POPular Genetics) trial tested a strategy of CYP2C19-guided antiplatelet therapy in 2,488 patients with ST-segment elevation myocardial infarction undergoing primary PCI, prescribing ticagrelor or prasugrel to CYP2C19*2 or *3 LOF allele carriers and clopidogrel to noncarriers, in comparison to a standard treatment arm in which all patients were prescribed ticagrelor or prasugrel. 17 The study showed a significant lower event rate for bleeding events in the genotype-guided arm, without increase in thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…Our results thus extend the previous demonstration that a rapid (<24h) CYP2C19-genotype-guided strategy for selection of P2Y12 inhibitor can reduce high-on treatment platelet reactivity (RAPID GENE study (19)) and ischemic events (PHARMCLO (20) and POPULAR GENETICS(18) studies) in CYP2C19*2 carriers. Indeed, in these three studies, CYP2C19 genotype was principally achieved with point-of-care genetic testing which provided results in 1 to 2 hours (18)(19)(20)(21) and consequently led to an adjusted antiplatelet therapy in the first day after genotyping (18). An important proportion of recurrent ischemic events occur in the immediate days following MI and PCI and a more rapid genotyping could therefore indicated a more rapid therapy adjustment during this high-risk period.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational (17) and randomized studies (18)(19)(20) have shown that CYP2C19 genotypeguided strategy for selection of oral P2Y12 inhibitors can reduce the increased thrombotic risk observed in CYP2C19 LOF carriers while limiting the incidence of bleeding associated with a systematic use of potent P2Y12 inhibitors. In these studies, CYP2C19*2 and 3 genotype was determined with point-of-care genetic testing or with on-site genetic analyzers which allowed a rapid (<24h in most cases) genotype assessment and drug adjustment (19)(20)(21). These techniques are however not accessible to all cardiology centers and it is currently unclear if the use of a routine CYP2C19 genotyping to tailor P2Y12 inhibitors in a real-world situation will be associated with a similar benefit .…”
Section: Introductionmentioning
confidence: 99%
“…The non-functional CYP2C19 ∗ 2 and ∗ 3 polymorphisms impair both antiplatelet effects and bioactivation of clopidogrel (Bergmeijer et al, 2018a; Klein et al, 2018). In the acute and non-acute settings, CYP2C19 genotyping is feasible and well used in everyday clinical practice (Bergmeijer et al, 2018b). Recently, beta-1,4-galactosyltransferase 2 c.909C>T gene variant was found which might be an independent genetic predictor of clopidogrel platelet reactivity (Pallet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%